2016
DOI: 10.1016/j.celrep.2015.12.072
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-Derived Proteases Escalate Inflammation through Activation of IL-36 Family Cytokines

Abstract: Recent evidence has strongly implicated the IL-1 family cytokines IL-36α, IL-36β, and IL-36γ as key initiators of skin inflammation. Similar to the other members of the IL-1 family, IL-36 cytokines are expressed as inactive precursors and require proteolytic processing for activation; however, the responsible proteases are unknown. Here, we show that IL-36α, IL-36β, and IL-36γ are activated differentially by the neutrophil granule-derived proteases cathepsin G, elastase, and proteinase-3, increasing their biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
321
2
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 278 publications
(348 citation statements)
references
References 43 publications
17
321
2
8
Order By: Relevance
“…2), most likely because of lack of N-terminal processing 35 . In agreement with previous findings 25,36 , IL-36 can be activated by proteases that are released by activated neutrophils, including elastase (Supplementary Fig. S7).…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…2), most likely because of lack of N-terminal processing 35 . In agreement with previous findings 25,36 , IL-36 can be activated by proteases that are released by activated neutrophils, including elastase (Supplementary Fig. S7).…”
Section: Discussionsupporting
confidence: 79%
“…This indicated that sufficient IL-17A was still present in these supernatants that stimulated gene expression. As mentioned above, IL-36 cytokines require processing to gain biological activity [34][35][36] . IL-36 can be processed and activated by proteases derived from neutrophils 25,36 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations